Inherited epidermolysis bullosa: A multisystem disease of skin and mucosae fragility - Guadalupe Maldonado-Colin; Carolina Hernández-Zepeda; Carola Durán-McKinster; María Teresa García-Romero (Wolters Kluwer Medknow Publications, 2017)
Epidermolysis bullosa (EB) is a blistering disorder that can be autosomic or dominantly inherited and has a wide spectrum of clinical presentations. The most recent classification divides EB into four basic subtypes: (1) EB simplex, (2) junctional EB, (3) dystrophic EB and (4) Kindler syndrome; depending on the level of the epidermal-dermal junction where the formation of blisters is present. With the use of immunohistochemistry and molecular biology, new mutation genes and proteins have been identified and more than thirty subtypes of EB have been described according to text phenotype, each affecting different key proteins for the structural integrity of the skin. The phenotype can be a mild one where blisters occur after minor trauma, but quality of life is preserved or a severe one with multisystemic manifestations affecting skin, mucous membranes, bones, joints, nutritional status, and cancer development leading to early death. We describe the clinical manifestations, diagnostic approach, and multidisciplinary management of EB subtypes.